A Systematic Implementation of the Waterfall Model in E-Commerce System Development for Small Businesses - Rakhmadi, Aris; Iqbal Firdaus, Malvin; Sulistyo Nugroho, Yusuf (Computing and Information System Journal, 2025)
The Waterfall model remains a widely used software development methodology, offering a structured, phase-driven approach to system development. This study applies the Waterfall model in developing a web-based e-commerce system for small businesses, aiming to improve business operations, usability, and system efficiency. The system was implemented for Anisha Klapertart and Cake to address manual sales and inventory management inefficiencies. Black Box Testing confirmed 100% functionality across core modules, including authentication, product management, and order processing. Usability testing using the System Usability Scale (SUS) with 30 respondents resulted in a score of 70.16, categorizing the system as "Good" and "Acceptable". Despite its benefits, challenges include limited adaptability to requirement changes and scalability concerns. Future enhancements will focus on integrating a payment gateway, improving security, and adding customer loyalty programs. These findings demonstrate the practicality of the Waterfall model in structured e-commerce development, offering valuable insights for small businesses transitioning to digital platforms.